Smart Technologies Applied to the Energy Sector. Renewable Energy Expansion Strengthened by Digital Communications and Distributed Ledger Technologies? - Silvia Serrano-Calle; Erik Delarue (International Telecommunications Society (ITS), 2018)
The development of variable renewable energy (VRE) and their massive installation are some of the challenges that the economies of a large part of the world will have to face in the coming years to help ensure a reasonable sustainability of the planet. On the other hand, the advances that have been happening in recent decades in the telecommunications sector and the expansion of the Internet have helped to create a new scenario, giving way to growth opportunities in different economic sectors and new business models. One of the most disruptive tools that has emerged in this new digital ecosystem is what is known as Distributed Ledger Technology (DLT). The opportunity and applicability to strengthen VRE expansion is discussed in this article. To this end, selected case studies and main findings of interviews with experts are discussed. The introduction of blockchain technology, in particular in its use as a platform for smart contracts, offers a great potential, highly valued by experts, in addition to adding other relevant characteristics such as efficiency generated in operational terms and traceability, but also new opportunities for consumers and prosumers to build strong energy communities committed with a sustainable energy transaction. However, among the elements to be improved, we highlight the regulatory uncertainty regarding smart contracts security in terms of automatic mechanisms and its legal endorsement for use within the EU; adopting standards to facilitate scalability; and other issues of a more technological nature that should also be improved for a massive implementation in terms of optimizing energy efficiency of the model.
Keywords: L86; O33; Q28; 330; Blockchain; Digital Policy; Energy Policy; Smart Energy; Sustainable Development Goals